Corporate Acquisitions: A Process Perspective - Jemison, David B.; Sitkin, Sim B. (Academy of Management Review, 1986)
Historically, acquisition scholars and practitioners have adopted a choice perspective which portrays the corporate executive analyzing acquisition opportunities as a rational decision maker. This paper suggests that the choice perspective be supplemented with a process perspective which recognizes the acquisition process itself as a potentially important determinant of activities and outcomes. A series of research propositions is offered suggesting how four impediments present in the process itself might affect acquisition outcomes.